Mekanisme Pertahanan Diri Tokoh Matara dalam Novel Mata di Tanah Melus Karya Okky Madasari : Kajian Psikologi Sastra (Humanis, 2026)
This research aims to describe the aspects identified as a form of self-defense mechanism that occurs in the main character Matara in the novel "Mata Di Tanah Melus" by Okky Madasari. This research is studied using Sigmund Freud's thoughts on self-defense mechanisms. According to Freud, self-defense mechanisms are efforts from the subconscious to defend themselves from threats or anxiety. To describe the findings, this research uses a qualitative descriptive method. The results of this study show that when Matara is experiencing anxiety due to a conflict, then spontaneously from her subconscious a response arises in the form of self-defense mechanisms. With this self-defense mechanism, Matara can regain her comfort from the threat of anxiety. There are four forms of self-defense mechanisms in Matara when facing a conflict, namely: denial self-defense mechanism, repression self-defense mechanism, formation reaction self-defense mechanism, and rationalization self-defense mechanism.
Keywords: Self defense mechanism; Okky Madasari novel; psychological study of literature; Sigmund Freud